Evaluasi Penggunaan Learning Management System Sebagai Alat Bantu Pembelajaran Matematika Sekolah Dasar - Kenny Jingga; Bernard Renaldy Suteja; Mewati Ayub (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Teaching and learning activities need to be interactive to increase children’s interest in learning. With the utilization of technology, there are so many learning tools had been made. One of them is Moodle. Moodle is a learning management system (LMS) application to support learning activity on electronic based (e-learning). The purpose of this research is to implement Moodle as LMS for mathematics learning on primary school children. By using Moodle, the lessons are delivered interactively for children to learn. This research will find out the influence of using this application towards the test score before and after using the application. T-Test analysis will be applied to analyze the differences. Besides analyzing the test score, questionnaires for the children who test the application will be given to know the effect of using the application for them. Based on the evaluation result using T-Test analysis, there were not any significant differences, but there were enhancements in average, highest, and lowest scores, along with the decrease in standard deviation. The result of correlation coefficient calculation between exercise frequency and quiz result was 0.2162, which meant that the correlation was weak or almost no correlation. Based on the questionnaire result, this application is considered helping children in understanding the subject.